2009
DOI: 10.1523/jneurosci.4179-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Mammalian Target of Rapamycin Signaling Pathway Suppresses Dentate Granule Cell Axon Sprouting in a Rodent Model of Temporal Lobe Epilepsy

Abstract: Dentate granule cell axon (mossy fiber) sprouting is a common abnormality in patients with temporal lobe epilepsy. Mossy fiber sprouting creates an aberrant positive-feedback network among granule cells that does not normally exist. Its role in epileptogenesis is unclear and controversial. If it were possible to block mossy fiber sprouting from developing after epileptogenic treatments, its potential role in the pathogenesis of epilepsy could be tested. Previous attempts to block mossy fiber sprouting have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
235
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(251 citation statements)
references
References 80 publications
(99 reference statements)
15
235
0
1
Order By: Relevance
“…When the mTOR inhibitor rapamycin, which is clinically used as an immunosuppressant, was administered after termination of SE, it blocked the chronic phase of mTOR activation and reduced mossy-fiber sprouting and the frequency of spontaneous seizures but not neurogenesis or neuronal death (Zeng et al, 2009). Suppression of SE-induced mossy-fiber sprouting by rapamycin has also been reported in the pilocarpine model of TLE (Buckmaster et al, 2009). However, suppression required continual treatment, and rapamycin treatment did not reverse already established axon reorganization (Buckmaster et al, 2009).…”
Section: Novel Approaches For Antiepileptogenesis In Post-status Epilmentioning
confidence: 73%
“…When the mTOR inhibitor rapamycin, which is clinically used as an immunosuppressant, was administered after termination of SE, it blocked the chronic phase of mTOR activation and reduced mossy-fiber sprouting and the frequency of spontaneous seizures but not neurogenesis or neuronal death (Zeng et al, 2009). Suppression of SE-induced mossy-fiber sprouting by rapamycin has also been reported in the pilocarpine model of TLE (Buckmaster et al, 2009). However, suppression required continual treatment, and rapamycin treatment did not reverse already established axon reorganization (Buckmaster et al, 2009).…”
Section: Novel Approaches For Antiepileptogenesis In Post-status Epilmentioning
confidence: 73%
“…Early results with the mTOR inhibitor rapamycin suggested that treatment with this immunosuppressant was disease-modifying in two different models of SE-induced epilepsy [18,19]. Furthermore, Zeng et al [20] found that rapamycin exerted an anti-seizure effect in a mouse model of tuberous sclerosis-a disease in which there is strong evidence supporting a role for the hyperactivation of the mTOR pathway in the pathology of tuberous sclerosis.…”
Section: Definitionsmentioning
confidence: 99%
“…[17][18][19][20][21] In other conditions, abnormal mTOR signaling has been implicated in the genesis of recurrent seizures, where it controls mossy fiber sprouting in the hippocampus. [22][23][24] Finally, recent studies have suggested that deregulated mTOR activation might underlie autistic-like behaviors in rodents. 25 Together, these observations highlight the essential role of mTOR in maintaining nervous system homeostasis both in health and in disease.…”
Section: Introductionmentioning
confidence: 99%